Quality of sexual life of women using the contraceptive vaginal ring in extended cycles: Preliminary report. (August 2014) - Caruso, Salvatore; Cianci, Stefano; Malandrino, Chiara; Cicero, Carla; Lo Presti, Lucia; Cianci, Antonio
Abstract Objective To evaluate the quality of the sexual life of healthy women who are using a contraceptive vaginal ring (CVR) in extended cycles. Methods Fifty-two women (18 to 32 years old) seeking hormonal contraception were enrolled in this prospective study. Women were to use a CVR releasing daily 15 μg of ethinylestradiol (EE) and 120 μg of etonogestrel (ENG) for 63 days, followed by a four-day hormone-free interval, for two such extended cycles. At baseline and at the first (day 63–73) and second (day 126–134) follow-ups the Female Sexual Function Index (FSFI) and the Short Form-36 (SF-36) questionnaires were administered to investigate, respectively, sexual behaviour and the quality of life (QoL). The Female Sexual Distress Scale (FSDS) was used to verify whether sexual dysfunction caused significant personal distress to the woman. Results The FSFI and FSDS scores obtained at the first and second follow-up appointments detected an improvement with respect to the baseline score (p < 0.05). QoL measures of body pain, general health and emotional role improved at the first follow-up visit (p < 0.05); at the second one, all variables showed improvement (p < 0.05). Conclusion According to these preliminary data the CVR in extended cycles could improve the sexual function and the QoL of women. Chinese Abstract 摘 要 目的 评估在扩展周期中使用阴道避孕环健康女性的性生活质量。 方法 寻求激素避孕的52名女性（18-32岁）参加了这项前瞻性研究。妇女使用阴道避孕环每天释放15μg炔雌醇和120μg依托孕烯, 共63天，随后4天是无激素间歇期，持续2个这样的周期。在基础状态及第一（63-73天）和第二（126-134天）周期，用女性性功能指数（FSFI）和简化SF-36表问卷，分别对性行为和生活质量(QoL)进行调查。使用女性性障碍量表(FSDS)来证明性功能障碍是否已经引起了明显的个人困扰。 结果 与基础评分相比，第一次和第二次随访时FSFI和FSDS评分明显提高（p＜0.05）。QoL评分 的身体疼痛，一般健康和情绪评分在第一次随访时明显提高；第二次随访时各项评分均明显提高。 结论 根据这些初步数据，扩展周期的阴道避孕环可能会改善性功能和提高妇女的生活质量。